A Brief Introduction to Judaism - Partridge, Christopher H. (Christopher Hugh), 1961-; Dowley, Tim (Book collections on Project MUSE., 2018)
This brief introduction to Judaism is designed to help readers understand this important religious tradition. Known and valued for its balanced approach, this text provides broad coverage of Judaism through an arresting layout with rich colors. The user-friendly content is enhanced by charts of religious festivals, historic timelines, updated maps, and a useful glossary. It is ideal for courses on Judaism and will be a useful, concise reference for all readers eager to learn more.